2022
DOI: 10.30604/jika.v7i2.1003
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Peppermint Aromatherapy on The Incidence of Emesis Gravidarum in The First and Second Trimester Pregnant Women in The Working Area of South Denpasar Public Health Center I, Denpasar City

Abstract: Emesis gravidarum is a condition that can cause weight loss, impaired body metabolism, malnutrition, weakness, and dehydration felt by the mother. Peppermint aromatherapy administered by inhalation can be a therapy that is able to overcome or eliminate nausea and vomiting in the first and second trimesters of pregnant women. The purpose of this study was to determine the effect before and after administering peppermint aromatherapy on the incidence of Emesis gravidarum in the first and second trimesters of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Peppermint aromatherapy has also shown potential in managing hyperemesis gravidarum, a condition characterized by excessive nausea and vomiting during pregnancy. A pre-experimental study found that peppermint aromatherapy significantly decreased the severity of these symptoms, promoting better health and nutrition during pregnancy [7]. Thus, peppermint aromas, either alone or in combination with other natural aromas like lavender and lemon could offer a safer, readily available alternative to potentially dangerous medication in conditions like hyperemesis gravidarum that require careful management due to their potential impact on both mother and child (foetus).…”
Section: Nausea and Vomitingmentioning
confidence: 99%
“…Peppermint aromatherapy has also shown potential in managing hyperemesis gravidarum, a condition characterized by excessive nausea and vomiting during pregnancy. A pre-experimental study found that peppermint aromatherapy significantly decreased the severity of these symptoms, promoting better health and nutrition during pregnancy [7]. Thus, peppermint aromas, either alone or in combination with other natural aromas like lavender and lemon could offer a safer, readily available alternative to potentially dangerous medication in conditions like hyperemesis gravidarum that require careful management due to their potential impact on both mother and child (foetus).…”
Section: Nausea and Vomitingmentioning
confidence: 99%